Screening Devices at School : The (Boundary) Work of Inclusion - Ratner, Helene (STS Encounters, 2011)
Including children with special needs in the common school has become an international political priority over the past 15-20 years. In reponse, new social technologies have emerged. This article analyses one such technology, an action plan called a SMTTE, and proposes that we understand it as a “screening device”. It is a “device” in the sense that it distributes agency, and it “screens” in the word’s multiple meanings: “projecting” as in creating a viewer position; “sifting” and “systematizing” as in discriminating “knowledge” from mere “opinionings”; and “protecting” teachers from noise. Using ethnographic data from a Danish school, the article explores, first, the script and agencement of the SMTTE and, second, how the screening properties of the SMTTE are achieved, including how these properties challenge management-teacher relations when the SMTTE travels to other networks at the school. The SMTTE does not form a seamless part of the school. Rather, its screening properties constitute their own trajectory, which interferes with other matters of concern at the school.